1729x-258=433x-474

Simple and best practice solution for 1729x-258=433x-474 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1729x-258=433x-474 equation:


Simplifying
1729x + -258 = 433x + -474

Reorder the terms:
-258 + 1729x = 433x + -474

Reorder the terms:
-258 + 1729x = -474 + 433x

Solving
-258 + 1729x = -474 + 433x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-433x' to each side of the equation.
-258 + 1729x + -433x = -474 + 433x + -433x

Combine like terms: 1729x + -433x = 1296x
-258 + 1296x = -474 + 433x + -433x

Combine like terms: 433x + -433x = 0
-258 + 1296x = -474 + 0
-258 + 1296x = -474

Add '258' to each side of the equation.
-258 + 258 + 1296x = -474 + 258

Combine like terms: -258 + 258 = 0
0 + 1296x = -474 + 258
1296x = -474 + 258

Combine like terms: -474 + 258 = -216
1296x = -216

Divide each side by '1296'.
x = -0.1666666667

Simplifying
x = -0.1666666667

See similar equations:

| (2/x^2+12x+36)+(5/x^2+x-30) | | X^2+10x+9=(x+1)(ax+b) | | -2(x-3)+4(2-x)= | | -5y-8=-7y-16 | | 19x-11-17x+14=2x+3 | | [5x-7]=33 | | 8-[(-3+7)-(3-9)]= | | 5+4x-7=4x-2 | | -10-(-3)= | | 0-8y=5 | | -4.07+2.3= | | T=C(2+AB) | | 5(2y+2)-(y+3)= | | abs(3x-4)= | | 1/3t-4/3=5/4t-3/2 | | 3(2x-1)-2(x-4)= | | 8m-5=6m-8 | | (5x-4)(4x+9)=0 | | 4(x+5)+3(x-6)= | | -136-10x=43-17x | | 45x^5+60x^2+15x= | | -2r+3=6-1/2r | | 1150+600+4x=800+400+9x | | x^2-14x-37=-8x+3 | | 1+3(-4z+7)=(z-8)-4 | | 1/2r | | m/n=p/q | | -v-4=3v | | 4(2x+3)-(x-2)= | | 2y/3-y/4=15 | | 2x^2+16x+32=17 | | 90x^2+84x^9+105= |

Equations solver categories